Micrasterias torreyi Bail. var. nurulislamii Aziz var. nov. (Chlorophyceae) from Bangladesh - Aziz, Abdul (Bangladesh Journal of Plant Taxonomy, 2010)
Not available. <span style="font-family: "Times New Roman"; font-size: 9pt; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: "Times New Roman"; mso-bidi-font-weight: bold;">Keywords:<span style="font-family: "Times New Roman"; font-size: 9pt; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: "Times New Roman"; mso-bidi-font-weight: bold;"> Micrasterias torreyi Bail. var. nurulislamii<span style="font-family: "Times New Roman"; font-size: 9pt; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: "Times New Roman";"> <span style="font-family: "Times New Roman"; font-size: 9pt; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: "Times New Roman";">Aziz var. nov.; Desmid; Green alga; Bangladesh. <span style="font-family: "Times New Roman"; font-size: 9pt; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: "Times New Roman";">DOI: 10.3329/bjpt.v17i1.5399 <span style="font-family: "Times New Roman"; font-size: 9pt; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: "Times New Roman";"><span style="font-family: "Times New Roman"; font-size: 9pt; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: "Times New Roman"; mso-bidi-font-size: 12.0pt;">Bangladesh<span style="font-family: "Times New Roman"; font-size: 9pt; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: "Times New Roman"; mso-bidi-font-size: 12.0pt;"> J. Plant Taxon. 17(1): 109-111, 2010 (June)